bvg Repression of alcaligin synthesis in Bordetella bronchiseptica is associated with phylogenetic lineage. - Giardina, P C (1995)
Recent studies have shown that Bordetella bronchiseptica utilizes a siderophore-mediated transport system for acquisition of iron from the host iron-binding proteins lactoferrin and transferrin. We recently identified the B. bronchiseptica siderophore as alcaligin, which is also produced by B. pertussis. Alcaligin production by B. bronchiseptica is repressed by exogenous iron, a phenotype of other microbes that produce siderophores. In this study, we report that alcaligin production by B. bronchiseptica RB50 and GP1SN was repressed by the Bordetella global virulence regulator, bvg, in addition to being Fe repressed. Modulation of bvg locus expression with 50 mM MgSO4 or inactivation of bvg by deletion allowed strain RB50 to produce alcaligin. In modulated organisms, siderophore production remained Fe repressed. These observations contrasted with our previous data indicating that alcaligin production by B. bronchiseptica MBORD846 and B. pertussis was repressed by Fe but bvg independent. Despite bvg repression of alcaligin production, strain RB50 was still able to acquire Fe from purified alcaligin, suggesting that expression of the bacterial alcaligin receptor was not repressed by bvg. We tested 114 B. bronchiseptica strains and found that bvg repression of alcaligin production was strongly associated with Bordetella phylogenetic lineage and with host species from which the organisms were isolated.